Optimum tie switches allocation and DG placement based on maximisation of system loadability using discrete artificial bee colony algorithm - Aman, M.M.; Jasmon, G.B.; Mokhlis, Hazlie; Bakar, Ab Halim Abu (Institution of Engineering and Technology, 2016)
Due to an exponential increase in load demand and lack of capital resources to improve the existing transmission line infrastructure, power utilities are focusing on methods to increase the efficiency and loadability of existing infrastructure. This study presents a new approach for simultaneous optimum distributed generation (DG) placement and optimum tie-switch allocation based on maximisation of system loadability using discrete artificial bee colony algorithm. The proposed algorithm is tested on 16-Bus, 33-Bus and 69-Bus radial distribution test system. The obtained results show that with simultaneous optimum DG placement and optimum tie-switch allocation, better results are achieved rather than solving two problems independently. Further it was also found that the proposed method has improved the efficiency of the system in terms of maximisation of system loadability, reduction in power system losses, improving the kVA margin to maximum loadability and voltage quality improvement.